A statistical study of poleward boundary intensifications (PBIs) associated with the arrival of polar cap patches - Fang, Yu-Lin; Xing, Zan-Yang; Zhang, Qing-He; Fang, Han‐Xian; Yang, Hui-Gen; Hu, Ze-Jun; Wang, Yong; Ma, Yu-Zhang; Lu, Sheng; Xiu, Zhi-Feng; Zhao, Bian-Long; Wang, Xiang-Yu; et al. (Frontiers in Astronomy and Space Sciences, 2026)
Poleward Boundary Intensifications (PBIs) are transient auroral brightenings at the poleward edge of the auroral oval that serve as optical tracers of nightside plasma transport and energy deposition. However, their statistical properties and coupling with solar wind and geomagnetic activity remain insufficiently understanding. Using the observations from Yellow River Station auroral All-Sky Imager during 2012–2024, we identified 1,225 PBIs that were specifically associated with nightside polar cap patches touching the poleward boundary of the auroral oval. This study investigated the spatiotemporal characteristics of PBIs and their relationship with interplanetary magnetic field (IMF) conditions and geomagnetic indexes. The key findings include: (1) PBIs predominantly occur between 21 and 01 magnetic local time (MLT), with a clear pre-midnight distribution; (2) Due to the modification by IMF By, PBIs occurrence exhibits a dawn-dusk asymmetry near 23 MLT, indicating a systematic longitudinal shift of the nightside ionospheric convection; (3) relative to substorm onset, the PBIs occurrence rate peaks within the 20–40 min window thereafter. These results provide quantitative evidence of IMF By modulating the MLT distribution of PBIs and establish PBIs as optical tracers of nightside plasma transport and energy deposition.